The Factors Affecting to Participatory of Community Business Management to Strengthen the Economic Foundation of the Public Policy of Loei Province - Maliton, Wich (Journal of Graduate MCU KhonKaen Campus, 2019)
The purposes of this research were: to study the factors effecting of public participation in community business management to strengthen the foundations of the economy according to the public policy. The population was 580 people. Samples were 337 people of sampled using R.V.Krejcic and D.W.Morgan samples. The sample size was determined by simple random sampling. The instruments used in the study were interview schedules, focus group discussion guides, and questionnaires. The statistics used for data analysis were percentage, mean, standard deviation Correlation coefficient. And, multiple regression analysis was applied by Enter method. The results of this research are as follows: 1) the study of factors affecting the participation of people in managing community business groups to strengthen the foundations of the economyaccording to public policy, it was found that (1) organic farming the most influential variables were participation in community activities Secondly, participation in the strengthening of the foundations economy. These variables together describe the change in the level of participation in community business management to strengthen the foundations of public policy based on 60.0% (R2= 0.600). (2) Community tourism the most influential variables were participation in community activities Secondly, participation in the strengthening of the economic foundation and career variables. These variables explain the changes in the level of participation in community business management in order to increase the strength of the grassroots economy by 67.6% (R2 = 0.676). (3) Processing products the most influential variables were participation in the strengthening of the foundations economy was followed by participation in community activities. And career variables. These variables explain the changes in the level of participation in community business management in order to strengthen the foundations of the public sector by 55.5% (R2 = 0.555).